‘For our self-sufficiency and autonomy’: International Worker Solidarity and the Global Networks of FOSATU in the Democratic Struggle in South Africa (Historia, 2023)
This article examines the place of the trade union movement in the democratisation project in South Africa. While scholarship exists which shows the role of the labour movement in the ending of apartheid, the focus tends to emphasise what has been called political or social movement unionism. However, one labour centre, the Federation of South African Trade Unions (FOSATU), pursuing a workerist approach to its trade unionism, created and extended tentacles of democracy during apartheid, outside the ambit and influence of political parties and the nationalist movement. FOSATU also created global networks and outreach in search of international worker solidarity. That solidarity was imperative for FOSATU’s self-sufficiency and autonomy as well as that of the broader anti-apartheid movement. The article argues that FOSATU broadened the platforms of the democratic struggle in South Africa beyond the nation-state boundary. In doing so, it contributes to the historiographies of the trade union movement, the struggle for democracy in South Africa and the transnational turn in the South African labour movement. The study uses the minutes and reports of FOSATU’s national executive, its central committee meetings and also news reports from the FOSATU Worker News, all of which are housed at Wits University’s William Cullen Library, in the Historical Papers section.
Keywords: FOSATU; democratic struggle; South Africa; international solidarity; trade unionism